Implementation of School Problem Solving Management in Improving School Achievement - Suparman, Asep; Sasongko, Rambat Nur; Kristiawan, Muhammad (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2021)
This qualitative study described the innovation regarding the application of principal problem solving management to improve school achievement. The results showed that the application of principal problem solving management can improve school achievement characterized by the number of awards received by schools, increased public interest and the existence of other schools that have comparative studies to school. The innovation of principal managerial dealing with various kinds of complex problems will be able to improve school achievement.